A risk stratification scheme for synchronous oligometastatic non-small cell lung cancer developed by a multicentre analysis. (April 2021) - Spaggiari, Lorenzo; Bertolaccini, Luca; Facciolo, Francesco; Gallina, Filippo Tommaso; Rea, Federico; Schiavon, Marco; Margaritora, Stefano; Congedo, Maria Teresa; Lucchi, Marco; Ceccarelli, Ilaria; Alloisio, Marco; Bottoni, Edoardo; et al.
Highlights: Oligometastatic NSCLC represents a category without a standard therapeutic approach. In selected oligometastatic NSCLC, radical surgery seems to offer a good prognosis. Treatment of selected synchronous oligometastatic NSCLC could be conducted safely. Abstract: Backgrounds: Oligometastatic Non-Small Cell Lung Cancer (NSCLC) patients represent a category without a standard therapeutic approach. However, in selected oligometastatic NSCLC, radical surgery seems to offer a good prognosis. This retrospective study aimed to analyse the long-term outcomes of synchronous oligometastatic patients treated with curative intent and identify the factors associated with better results and the proposal of a risk stratification system for classifying the synchronous oligometastatic NSCLC. Methods: The medical records of patients from 18 centres with pathologically diagnosed synchronous oligometastatic NSCLC were retrospectively reviewed. The inclusion criteria were synchronous oligometastatic NSCLC, radical surgical treatment of the primary tumour with or without neoadjuvant/adjuvant therapy and radical treatment of all metastatic sites. The Kaplan – Meier method estimated survivals. A stratified backward stepwise Cox regression model was assessed for multivariable survival analyses. Results: 281 patients were included. The most common site of metastasis was the brain, in 50.89 % patients. Median overall survival was 40 months (95 % CI: 29–53). Age ≤65 years (HR = 1.02, 95 % CI: 1.00–1.05; p = 0.019), single metastasis (HR = 0.71, 95 % CI: 0.45–1.13; p = 0.15) and presence of contralateral lung metastases (HR = 0.30, 95 % CI: 0.15 – 0.62; p = 0.001) were associated with a good prognosis. The presence of pathological N2 metastases negatively affected survival (HR = 2.00, 95 % CI: 1.21–3.32; p = 0.0065). These prognostic factors were used to build a simple risk classification scheme. Conclusions: Treatment of selected synchronous oligometastatic NSCLC with curative purpose could be conducted safely and at acceptable 5-year survival levels, especially in younger patients with pN0 disease.